(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This paper reports regarding an self-determining hurdle avoiding robotic vehicle which is directed with help of a ultrasonic sensors . Arduino micro-controller manages the hurdle deviator and is constructed by the ultrasonic sensor. In front part of the deviator the ultrasonic sensors is firmed . By help of the sensors held in front side deviator fetches the data . Thus the sensor recoginizes the hurdle and alters the way to choose the free way . The I/P is sent by sensing element to controller and compares by assistance of the controller to determine the motion of the obstacle deviator.